Nuancing the roles of entrepreneurial universities in regional economic development. Issue 5 (4th May 2022) - Pugh, Rhiannon; Hamilton, Eleanor; Soetanto, Danny; Jack, Sarah; Gibbons, Amy; Ronan, Nicola
ABSTRACT: This paper explores the idea of the entrepreneurial university and how it differs in diverse regional and institutional settings. From the analysis of university engagement in a regional economic development programme in fifteen city-regions in England (UK), this study identifies three roles that entrepreneurial universities play in regional economic development as growth supporter, steerer, and driver. The roles vary depending on regional characteristics, the university's motivation and its capability to engage in third mission activities and the constellation of active stakeholders working towards regional development. In addition to advancing the concept of entrepreneurial universities, this paper explores the contemporary policy trend towards placing a stronger emphasis on universities as drivers of regional economic development.